A Community-Based Music Therapy Support Group for People With Alzheimer's Disease and Their Caregivers: A Sustainable Partnership Model - Rio, Robin (Frontiers in Medicine, 2018)
Abstract People with Alzheimer's and related dementias and their family caregivers who reside at home have unique strengths and needs. They have the strength of being in a place with which they are familiar, with people they are in close relationship. Often it is the spouse who provides the primary care of their loved one, and as the disease progresses both members of the couple are at risk for depression, isolation, and decreased contact with peers and community networks that would help maintain sociocultural, intellectual, physical, sensory and spiritual needs. The person with AD is losing life skills and sense of self as their memory loss worsens, and the caregiver loved one, which may be a spouse, relative, or close companion, is becoming increasingly burdened physically and emotionally. Meaningful support in a community-based peer group can meet the needs of the person with dementia and their care partner from the first symptoms through the middle to later stages of AD, through a carefully designed music therapy program tailored to preference, culture, and ability. The music therapist working in the community provides practical leadership in coordination with local agencies, is an experienced clinician with an understanding of the needs of the person with dementia and their carer from both a neurological and psychosocial perspective, and is creatively equipped in all facets of musical engagement for health and wellness, including cognitive/intellectual, socio-emotional, cultural, physical and spiritual support.